Fiscal insurance and public debt management: Evidence for a large emerging economy - Helder Ferreira de Mendonça; Kelli Manh\~aes Pessanha (EconomiA, 2014)
This paper is a contribution to the analysis concerning fiscal insurance and public debt management. We built fiscal indicators and present empirical evidence for the effect of the public debt management on the fiscal insurance based on the Brazilian economy. The analysis is based on two steps: the first builds fiscal indicators and analyzes their performance over time, and the second presents regressions of the main variables regarding public debt management on the fiscal insurance indicators. The findings denote that there was a reduction in the fiscal vulnerability, but the public debt management was not effective in increasing fiscal insurance. – – Este artigo é uma contribuiç\~ao à análise sobre a segurança fiscal e o gerenciamento da dívida pública. Com base na economia brasileira foram construídos indicadores fiscais e apresentadas evidências empíricas referentes ao efeito do gerenciamento da dívida pública sobre a segurança fiscal. A análise é realizada em duas etapas: a primeira constrói indicadores fiscais e analisa o desempenho ao longo do tempo; e a segunda apresenta regress\~oes das principais variáveis relativas ao gerenciamento da dívida pública sobre os indicadores de segurança fiscal. Os resultados denotam que houve uma reduç\~ao da vulnerabilidade fiscal, mas o gerenciamento da dívida pública n\~ao foi efetivo para aumentar a segurança fiscal.
Keywords: E43; E62; H62; H63; 330; Fiscal insurance; Public debt management; Fiscal indicators; Brazil